Interpersonal Communication and Work Productivity: A Case Study on Effective Communication at PT. Aseanindo Network Solutions - Salmabila Dwiyanti; Farida Nurfalah; Yanto Heryanto (Siber Nusantara of Law and Politic Review, 2026)
Interpersonal communication plays an important role in building and increasing work productivity in an organization. This research aims to understand the interpreted and applied interpersonal communication in supporting work productivity and identifying obstacles that occur through case studies at PT. Aseanindo Network Solutions This research uses a qualitative method with a case study approach, data is collected through in-depth interviews with HRD managers and employees. While data analysis uses the Miles and Huberman interactive model which includes three stages, namely data reduction, data presentation, and drawing conclusions. The research results show that effective interpersonal communication is understood by informants as an important factor in supporting smooth work, creating a harmonious working relationship, and reducing potential problems in the work environment. This finding is in line with Joseph Devito 1989's interpersonal communication theory which emphasizes the importance of openness, empathy, supportive attitude, positive attitude, and equality in work interaction. However, there are still several communication barriers, such as miscommunication and differences in perception between individuals, which have the potential to hinder the smoothness of work and reduce productivity. Therefore, improving the quality of interpersonal communication needs to be done sustainably to support the achievement of organizational goals.